Prospects of rhizobial inoculant technology on Bambara groundnut crop production and growth - Fwanyanga, Felicitas M.; Horn, Lydia N.; Sibanda, Timothy; Reinhold-Hurek, Barbara (Frontiers in Agronomy, 2022)
After peanuts and cowpeas (Vigna unguiculata), the Bambara groundnut (Vigna subterranea (L.) Verdc) is the third most significant food legume in Africa. It is characteristically grown in marginal soils, is drought tolerant, and also has the potential for nitrogen fixation. Despite that, year-on-year Bambara groundnut yields are on a gradual decline due to a combination of abiotic and biotic stresses such as uneven annual rainfall and climate-induced changes in soil microbial community compositions, negatively impacting food security. Thus, the application of rhizobial inoculants at planting significantly improves yields in many leguminous crops. Moreover, symbiotic inoculants are well established in developed countries for improving nitrogen fixation and productivity in grain legumes. Sub-Saharan African countries, however, still under-utilise the above practice. In crop production, nitrogen (N) is the most frequently deficient nutrient since it stimulates root and shoots growth. Whereas nitrogen fertilisers can be used to supplement soil N levels, they are, however, also costly, at times inadequate, may not be timely in supply and may have deleterious environmental consequences. Hence, rhizobial inoculants are seen as a cheaper, easier, and safer method for improving N-fixation and crop productivity in grain legumes, as a result, smallholder farming systems are food secure. Thus, identifying the most efficient rhizobial strains for biofertiliser production for Bambara groundnut is of utmost importance to the farming communities.